2020
DOI: 10.1101/2020.08.22.262634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-component multilayered self-assembling nanoparticles presenting rationally designed glycoprotein trimers as Ebola virus vaccines

Abstract: The Ebola virus (EBOV) glycoprotein (GP) can be recognized by neutralizing antibodies (NAbs) and is the main target for vaccine design. We first investigated the contribution of the stalk and the heptad repeat 1-C (HR1C) region to GP metastability. Specific stalk and HR1C modifications in a mucin-deleted form (GPΔmuc) increased trimer yield, while alteration of HR1C exerted a more complex effect on thermostability. Crystal structures were determined to validate these rationally designed GPΔmuc trimers in their… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(47 citation statements)
references
References 108 publications
(199 reference statements)
4
43
0
Order By: Relevance
“…1J). Previously, we genetically fused a small LD protein and a T-cell epitope to each subunit of the E2p and I3-01v9 60-mers, resulting in "multilayered" SApNPs (60). PADRE, a 13-aa pan-DR epitope that activates CD4 + T cells (74), was used to promote B cell development toward NAbs.…”
Section: Rational Design Of Scaffolded Rbd Trimers and Rbd-presenting Sapnpsmentioning
confidence: 99%
See 4 more Smart Citations
“…1J). Previously, we genetically fused a small LD protein and a T-cell epitope to each subunit of the E2p and I3-01v9 60-mers, resulting in "multilayered" SApNPs (60). PADRE, a 13-aa pan-DR epitope that activates CD4 + T cells (74), was used to promote B cell development toward NAbs.…”
Section: Rational Design Of Scaffolded Rbd Trimers and Rbd-presenting Sapnpsmentioning
confidence: 99%
“…Recent cryo-EM and cryo-ET studies revealed that the SARS-CoV-2 spikes could adopt diverse orientations on native virions due to the highly flexible HR2 stalk (54)(55)(56). Previously, we identified an HR1 bend as the cause of HIV-1 Env metastability (58,81) and examined the role of an equivalent HR1 bend and the HR2 stalk in EBOV GP metastability (60). This understanding of metastability proved critical for designing stable trimers and trimer-presenting SApNP vaccines for both viruses (58)(59)(60)81).…”
Section: Rational Design Of Prefusion Spike Through Minimizing Metastabilitymentioning
confidence: 99%
See 3 more Smart Citations